Orientation Training Development for Gereja Bethel Indonesia Rayon 3 Fulltimers - S. Kurniadi; R. Pramono (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Human resources are one of the important resources owned by the church. Orientation training is an important activity. This study aims to develop an orientation training program for fulltimers of the Indonesian Bethel Church Jl Jenderal Gatot Subroto Rayon 3 in an effort to improve organizational culture and reflective thinking skills. The research and development of this training uses the model from Borg and Gall. The results of the research also produce training media products in the form of print media and training videos. The results of the needs analysis show that there is a need for employee orientation training by using good learning media to improve the knowledge, abilities, and attitudes of fulltimers. Meanwhile, the results of the initial product feasibility test have an average value of 87.7 percent meaning the product can be used with minor revisions. While the test results show an average value of 85, this value is above the minimum completeness value. The final result of this research is a training program with a 191-page training module with four training videos